Seven Views on the Meaning of 'Europe'. Issue 1 (13th June 2018) - Freigang, Christian; Kurg, Andres; Tostões, Ana; Popescu, Carmen; Dettingmeijer, Rob; Stieber, Nancy; Mengin, Christine
Abstract : The first part of these field notes consists of three perspectives from Germany, Estonia, and Portugal on the meaning of 'Europe' for the historiography of architecture. The second part contains four reflections on the history and role of the EAHN in opening new and inclusive venues of inquiry vis-à-vis the fragile concept of 'Europe'.